Henry James, painters, and painting - Seager, Z (2019)
In his major essay “The Art of Fiction” (1884) Henry James suggested that the analogy between painting and fiction was, so far as he could see, ‘complete’. Taking him at his word, critics have tended to focus on what the novelist learned from painting, or have fixed on instances in which he ‘chose to elevate the art of the painter,’ as one commentator has recently put it. Contrary to this critical trend, this thesis argues that throughout his corpus James stages a contest between painting and fiction, consistently emphasising the ways in which the latter ought to be considered the superior art. This formed part of a broader programme in which the novelist sought to demonstrate the value and intellectual seriousness of fiction – still in jeopardy in the nineteenth century – by contrasting it with painting. This thesis therefore seeks to revise the ways in which criticism has approached James’s use and appreciation of the painter’s art. It shifts both the terms and the focus of the debate: away from broad correspondences between James’s work and artistic movements such as Impressionism and towards a finer understanding of the novelist’s unique response to painting; away from the supposedly controlling presence of critics such as John Ruskin or Walter Pater and towards the uses to which James put his conception of the painter’s art. In this way, the thesis amends longstanding ideas about the novelist’s response to and communication with painters and painting. At the same time, it reveals through the eyes of a major writer some of the ways in which painting and fiction corresponded in the period. In foregrounding the contexts which animated James’s work – from his negotiation of the transatlantic literary marketplace to his abiding interest in France and the French language, from issues of gender and portraiture to his response to Romantic painting, Pre-Raphaelite art, the Barbizon School, and Impressionism proper – the intention is to elucidate the inner workings of the novelist’s oeuvre. Each chapter is therefore built around a close focus on James’s most consistent passion, his most profound practice: the art of fiction.